MEMBANGUN MINDSET WIRAUSAHA SEJAK REMAJA - Andi Alfianto Anugrah Ilahi; Hasbiyah Srianah Amir, Darmawansah Ibrahim (Adiba Aisha Amira, 2025)
In the era of globalization and rapid technological development, the decline in youth entrepreneurship is a serious challenge in various countries, including Indonesia. One strategic solution to overcome this problem is to develop an entrepreneurial mindset from adolescence. An entrepreneurial mindset encompasses not only the ability to create a business but also fosters a creative, innovative, independent, and resilient attitude in facing challenges. This article aims to examine the importance of early entrepreneurship education and training, particularly among adolescents, through curriculum approaches, training, and the role of family and school environments. By fostering an entrepreneurial spirit from adolescence, it is hoped that the younger generation can become independent economic actors capable of creating jobs, improving community welfare, and contributing to national economic development. This study uses a descriptive qualitative approach with literature review and field observation methods. The results indicate that cultivating the habit of creative thinking, the courage to take risks, and active involvement in entrepreneurial activities can shape a productive and solution-oriented mindset in adolescents.